Case study: Dynamic performance of a MTDC network in Zhoushan city - Xu, Z.; Zhang, C. (Elsevier, 2016)
This paper presents dynamic responses of a multi-terminal high voltage DC (MTDC) network in Zhoushan islands, China. The conventional methods of controlling MTDC networks suffered from poor dynamic performance. In this paper, an optimal strategy is derived through three main steps: DC load flow, optimum power flow and N-1 security for MTDC networks. The strategy is fulfilled by incorporating the loss minimization in a MTDC network. The advantages of the strategy are verified by dynamic simulations using MATLAB/Simulink package.